CARROT FARMING (DAUCUS CARORA L.) AT PT FUJITAKE SHOUTEN CO., LTD., NAGASAKI PREFECTURE, JAPAN - Farah Nur Syahida; Neneng Kartika Rini; Endang Tri Astutiningsih (UIN Sunan Gunung Djati Bandung, 2026)
This study analyzes the production system and economic feasibility of carrot farming (Daucus carota L.) at PT Fujitake Shouten Co., Ltd., Nagasaki Prefecture, Japan. A descriptive quantitative approach was applied using observation, interviews, and documentation. The production system includes land preparation, planting, maintenance, harvesting, and post-harvest handling across two production cycles per year. The results show that annual production ranges from 300,000 to 400,000 kg. The total production cost is IDR 400,000,000 per year, while total revenue reaches IDR 500,000,000. The net income obtained is IDR 100,000,000 per year. The R/C ratio of 1.25 indicates that the farming system is economically feasible, as revenue exceeds total costs. The B/C ratio of 0.25 reflects moderate efficiency influenced by multi-activity farm operations and post-harvest processes such as sorting and packaging. Overall, the study concludes that efficient input management and a well-structured production system are essential to maintain farm sustainability and economic performance.